LITERAT MELALUI PRESENTASI - Lisnawati, Iis; Ertinawati, Yuni (Universitas Siliwangi, 2019)
The literacy ability of the Indonesian nation is still not in line with expectations. One solution to the problem is to integrate literacy in learning, especially presentation learning. Therefore, the purpose of this study is to describe the integration of literacy in the presentation of learning to students in universities. The method used in this research is descriptive qualitative method. The form of integrating literacy in presentation learning is by using an eclectic type of literacy (early literacy, basic literacy, library literacy, media literacy, technology literacy, or visual literacy) according to the needs at each stage of speaking, either at (1) pre-speaking stage, (2) speaking stage, and (3) post-speaking stage. Implementation of learning is done cooperatively student and stdent, collaboratively between student, lecturer, and instructor and interaction between student, lecturer, instructor, and learning materials. Thus, this strategy is expected to build a multiliterat and multicompetence students.